2019
DOI: 10.1164/rccm.201801-0204pp
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea and the Risk of Cognitive Decline in Older Adults

Abstract: Obstructive sleep apnea causes intermittent hypoxia and sleep fragmentation and affects at least 20% of individuals after the age of 65. There is accumulating evidence that obstructive sleep apnea may impact brain structure and function. Recent cohort studies suggest that it is a risk factor for stroke, mild cognitive impairment and Alzheimer's disease. Because prevention through treatment of risk factors is currently the main intervention for reducing the incidence of dementia, how obstructive sleep apnea aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 73 publications
3
71
0
2
Order By: Relevance
“…Whilst there is an adverse impact of OSA on the healthy young brain, and this is greater with the aging middle-aged brain [41], the natural assumption is that the additive burden of OSA may exert greater deleterious effects especially to the elderly brain. Untreated OSA can potentially accentuate the progression of MCI and Alzheimer's disease [2] in cognitively intact individuals due the accumulation of Alzheimer's disease biomarkers (amyloid beta and tau proteins) [42,43], through hypoxic insults and/or disrupted sleep architecture [39].…”
Section: Evidence On Association Between Osa and MCImentioning
confidence: 99%
“…Whilst there is an adverse impact of OSA on the healthy young brain, and this is greater with the aging middle-aged brain [41], the natural assumption is that the additive burden of OSA may exert greater deleterious effects especially to the elderly brain. Untreated OSA can potentially accentuate the progression of MCI and Alzheimer's disease [2] in cognitively intact individuals due the accumulation of Alzheimer's disease biomarkers (amyloid beta and tau proteins) [42,43], through hypoxic insults and/or disrupted sleep architecture [39].…”
Section: Evidence On Association Between Osa and MCImentioning
confidence: 99%
“…Recent meta‐analyses concluded that OSA is a risk factor for cognitive decline and incident dementia (Leng, McEvoy, Allen, & Yaffe, ; Shi et al, ; Zhu & Zhao, ). These epidemiological findings have given rise to several mechanistic hypotheses linking OSA to neurodegeneration: OSA is associated with amyloid‐β generation and altered clearance, tau hyperphosphorylation, inflammation, oxidative stress, and metabolic and vascular deregulation (Baril, Carrier, et al, ; Baril, Gagnon, et al, ; Gosselin, Baril, Osorio, Kaminska, & Carrier, ; Polsek et al, ; Rosenzweig et al, ). In addition, OSA in late middle‐aged and older adults could precipitate the progression toward dementia by creating microstructural cerebral changes, especially white matter damage.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Long-standing OSA leads to recurrent intermittent hypoxia and alters sleep architecture, which may lead gradually to brain neurodegenerative processes. 39 A recent review proposed several possible mechanisms linking OSA to dementia, highlighting the important roles chronic sleep architecture impairments may play in neurogenesis, synaptic plasticity and memory consolidation. 39 A neuroimaging meta-analysis assessing the neuro-structural differences between patients with OSA and healthy controls reported significant grey matter reductions in the bilateral parahippocampus, left temporal and right frontal lobes of OSA patients.…”
Section: Evidence On Association Between Osa and MCImentioning
confidence: 99%
“…39 A recent review proposed several possible mechanisms linking OSA to dementia, highlighting the important roles chronic sleep architecture impairments may play in neurogenesis, synaptic plasticity and memory consolidation. 39 A neuroimaging meta-analysis assessing the neuro-structural differences between patients with OSA and healthy controls reported significant grey matter reductions in the bilateral parahippocampus, left temporal and right frontal lobes of OSA patients. 40 Whilst there is an adverse impact of OSA on the healthy young brain, and this is greater with the aging middle-aged brain 41 , the natural assumption is that the additive burden of OSA may exert greater deleterious effects especially to the elderly brain.…”
Section: Evidence On Association Between Osa and MCImentioning
confidence: 99%